ANALYSIS OF THE INTERRELATION BETWEEN LANGUAGE AND CULTURE (USING THE EXAMPLE OF THE ENGLISH LANGUAGE) - Ochilboyeva Iroda Alisher qizi (Research Focus International Scientific Journal, 2025)
This article explores the interrelation between language and culture, using the English language as an example. It examines how language reflects cultural characteristics and how cultural changes influence linguistic development. The study analyzes the communicative, cognitive, and cultural functions of language, demonstrating its role as a carrier of cultural values, traditions, and societal norms. The impact of historical events, globalization, and technological advancements on the evolution of English is also discussed. By examining idioms, neologisms, dialects, and expressions, the article highlights the dynamic interaction between language and culture, emphasizing the importance of linguistic diversity and cultural identity.